Process Improvement and ICTs in Australian SMEs: a Selection and Implementation Framework - Nousala, Susu; Ifandoudas, Panayiotis; Terziovski, Mile; Chapman, Ross (Taylor & Francis, 2008)
This article describes the development, modification and testing of a tool designed to assist small firms in making more appropriate decisions regarding information and communication technology (ICT) selection and implementation. Using a combination of quantitative and qualitative methods, a number of possible tools were initially developed to support firm-based self-diagnostic exercises. Research outcomes from a joint European–Australian research project were regionalised for Australian conditions through collaborative product development with a number of Australian SME manufacturing firms. This article reports on the pilot implementations and the outcomes achieved with these Australian SMEs. These implementations have shown successful outcomes for the trial SME participants and have led to the creation of an online self-assessment tool to allow wider access by interested SMEs.